Proceso de comercialización del cacao en Asociación de Productores Agrícolas la Revancha del Recinto San José - Carpio Cortéz, Juliana Lisbeth (2020)
Agricultural activities represent an important axis of work that stimulates the popular and solidarity economy, which is why its value chain is an important point of analysis, due to the fact that on repeated occasions the guarantees of adequate trade that promote social development and The economic benefits of the farmers are null, this is the importance of analyzing the commercialization process in the Association of Agricultural Producers La Revancha of the San José enclosure belonging to the Febres Cordero Parish, with the premise of determining what are the main inconveniences that the association has in the commercial management of cocoa production. The methodology used has the types of descriptive and field investigations, which allowed obtaining data in primary sources for later; The method used is the inductive one accompanied by the use of the survey as a technique, which allowed determining as the main conclusions the scarce organization in the members of the association, production sold to intermediaries with inadequate prices, absence of a distribution logistics that contributes with a direct distribution channel with export companies or national industries, few training processes on technical assistance for cultivation and principles of administration and development of activities in an empirical way that makes it impossible to properly manage the organization's resources or obtain production processes with quality indicators different from those demanded by the consumer market.